The Great Recession and Developing Countries : Economic Impact and Growth Prospects - Nabli, Mustapha K. (World Bank, 2012)
While globalization has been a powerful engine of economic growth over the past three decades, it has also posed new problems and challenges, especially for international economic policy coordination. In the past decade, the large and rapid increases in trade, remittances, and international financial flows across borders have been a strong incentive for economic growth, not only in East and South Asia but also in Latin America and Sub-Saharan Africa. And rapid and sustained economic growth in several low- and middle-income economies has been steadily altering the economic weights of different regions in the world economy. The ten case studies in this volume illustrate the wide range of effects of, and responses to, the global crisis in low-and middle-income economies. While the case studies do not constitute a statistically representative sample of the globe, they illustrate a broad range of experiences in the wake of the crisis and give insights into both the benefits and challenges of globalization. The use of a common methodology in preparing the cases unquestionably facilitates cross-country comparisons and helps identify areas where more study is needed to increase the understanding of the current problems of, and prospects for, developing countries.